Communicative practices of young people in social networks - S. A. Grishaeva; K. V. Klyuvaev (Цифровая социология)
Modern young people more and more often spend their time on social media, which they use for place for friendly chat, or place to spend leisure time, or place for buying things, or space for professional growth, or one of many other reasons. In the process of interaction, youth use various communication practices in social networks, the main of which have been given in the article.Main functions of social media, specifics and classification of user communities, their influence on communicative behavior of users have been described. Instruments of transferring social information on social media: emoji and stickers, photos and pictures (memes included), together with preferences of usage of this instrument by users have been analyzed. It has been proved, that peculiarities of lexis typical for virtual communication along with non-verbal means (such as memes) transform the language of users.The phenomenon of fake (an account hiding the real essence of a user), as well as reasons for creation of fake accounts and their functionality, have been considered. Degree and form of showing aggression in virtual communication have been analyzed. Specifics of content in dependence from typology of social communities, where users are interacting (groups by interest, groups with entertaining content, news communities, official companies groups, e-commerce pages, groups of citizens of a specific city (or workers of a specific place), help groups, blog communities) has been studied. Common regularities of both creation and usage of content in internet communities have been noted.